In assisted reproduction by IVF or ICSI, the rate at which embryos develop to the blastocyst stage is influenced by the fertilization method used: a split IVF/ICSI study - Speyer, Barbara (J Assist Reprod Genet, 2019)
PURPOSE: To compare in vitro fertilization (IVF) with intracytoplasmic sperm injection (ICSI) in regard to post-fertilization development and outcome with the purpose of ascertaining the most effective fertilization method for assisted reproduction. METHODS: A retrospective cohort study of 136 split IVF/ICSI cycles (where sibling oocytes are fertilized by two different methods using the same sperm sample). RESULTS: IVF-derived embryos developed to the blastocyst stage at a significantly faster rate than ICSI-derived embryos. There was no significant difference in fertilization or livebirth rates between the two fertilization methods. CONCLUSIONS: For patients with sperm progressive motility ≥ 1.0 × 10(6)/ml (who usually constitute the majority of patients), no significant difference between the two fertilization methods was found in regard to fertilization rate or livebirth rate. Remaining factors influencing choice between the two methods appear to be restricted to convenience, financial considerations and concern with regard to possible perpetuation of genetically linked infertility to future generations.